Platelets contribute to disease severity in COVID‐19. (29th September 2021) - Barrett, Tessa J.; Bilaloglu, Seda; Cornwell, Macintosh; Burgess, Hannah M.; Virginio, Vitor W.; Drenkova, Kamelia; Ibrahim, Homam; Yuriditsky, Eugene; Aphinyanaphongs, Yin; Lifshitz, Mark; Xia Liang, Feng; Alejo, Julie; et al.
Abstract: Objective: Heightened inflammation, dysregulated immunity, and thrombotic events are characteristic of hospitalized COVID‐19 patients. Given that platelets are key regulators of thrombosis, inflammation, and immunity they represent prime candidates as mediators of COVID‐19‐associated pathogenesis. The objective of this study was to understand the contribution of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) to the platelet phenotype via phenotypic (activation, aggregation) and transcriptomic characterization. Approach and Results: In a cohort of 3915 hospitalized COVID‐19 patients, we analyzed blood platelet indices collected at hospital admission. Following adjustment for demographics, clinical risk factors, medication, and biomarkers of inflammation and thrombosis, we find platelet count, size, and immaturity are associated with increased critical illness and all‐cause mortality. Bone marrow, lung tissue, and blood from COVID‐19 patients revealed the presence of SARS‐CoV‐2 virions in megakaryocytes and platelets. Characterization of COVID‐19 platelets found them to be hyperreactive (increased aggregation, and expression of P‐selectin and CD40) and to have a distinct transcriptomic profile characteristic of prothrombotic large and immature platelets. In vitro mechanistic studies highlight that the interaction of SARS‐CoV‐2 with megakaryocytes alters the platelet transcriptome, and its effects are distinct from the coronavirus responsible for the common cold (CoV‐OC43). Conclusions: Platelet count, size, and maturity associate with increased critical illness and all‐cause mortality among hospitalized COVID‐19 patients. Profiling tissues and blood from COVID‐19 patients revealed that SARS‐CoV‐2 virions enter megakaryocytes and platelets and associate with alterations to the platelet transcriptome and activation profile.